Youth Leaders and the Arts: From Conflict to Strategic Community Building: Líderes Juveniles y las Artes: Del Conflicto a la Construcción Estratégica de Comunidades - Fisher-Yoshida, Beth; Lopez, Joan; Civico, Aldo (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
The objective of this paper is to suggest that conflict, peacebuilding and states of peace are the products of the intimate social relationships that are at work in a society between individuals and social institutions, such as governments, armed forces (legal and illegal), grassroots organizations, gangs, and so forth; and most importantly, that it is the social imagination that we attach to such relationships that produce and reproduce the patterns that can, on the one hand produce and sustain conflict, or on the other hand, produce and sustain conditions upon which a process of peacebuilding can be constructed. In sum, we want to suggest that within the intricacy of the social networks that produce patterns of conflict, exist the elements to transform these patterns into those of its sustainable resolution. Lo que queremos sugerir por medio de este trabajo es que la consolidación de un estado de paz es posible mediante a la re-organización de las relaciones sociales entre individuos e instituciones, como gobiernos, fuerzas armadas (legales e ilegales), organizaciones no gubernamentales, pandillas, etc. También es importante recalcar que es en la imaginación social que atribuimos a las relaciones que producen y reproducen patrones de conflicto por un lado, y patrones de construcción de la paz por el otro, donde existe el mayor potencial de cambio social. En resumen, queremos sugerir que dentro de la complejidad del tejido social que produce patrones de conflicto y patrones de resistencia, existen los elementos para producir y fortaleces patrones que conllevan a la construcción de una paz sostenible.